The Length of Onboarding Processes and Their Impact on Employee Efficiency - An Outline of Empirical Research - Krzysztof WĄSEK (Communications of International Proceedings, 2022)
In this article, the author discusses the essence of onboarding programmes and their duration. The time during which new employees gain knowledge about the new organization varies greatly in many cases. The aim of the author of the paper is to present the author's research direction. The paper also addresses the issue of the levels of implementation that a new employee can achieve by implementing the assumptions of the onboarding programme.
Keywords: onboarding; organizational socialization; adaptation of employees.